On Grimm's conception of sound-shift and generative phonology - Farid M. Onn., (Universiti Kebangsaan Malaysia, 1980)
The name Jacob Grimm (1785-1863) is a household word for historical-linguistics. His conception of the consonant shift, which was formalized as Grimm's Law, had made a great impact on linguistics. In this paper we discuss his sound shift law as a unit and assess the relevance of this law to the concept of linguistic (phonological) change as it is understood and practiced by linguists committed to the conception of language and grammar implicit in the theory of generative grammar.